THE CONSTRUCTION OF THE COSTA RICAN MEDIA CRIMINAL POLICY THROUGH THE “DIARIO EXTRA” NEWSPAPER - Trejos Robert, Sergio (2022)
Studying the treatment of the crime phenomenon made by the mass media is one of the new challenges of criminology. These for-profit companies convey a distorted image of criminality and the criminal system. Through the study of all the headlines on the cover of the Diario Extra published during 2017, the image of the crime transmitted by this mass communication media will be studied - empirically -.